An analysis and Design of An Automated Dashboard technologies for developing web based applications - BHAIKENOTES - et.al, Vivek Singh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Dashboard are relied upon to improve dynamic by enhancing cognizance and gaining by human perceptual capacities. Subsequently, premium in dashboards has expanded as of late, which is additionally obvious from the expansion of dashboard arrangement suppliers on the lookout. Regardless of dashboards' fame, little is thought about the degree of their viability, for example what sorts of dashboards turn out best for various clients or undertakings. In this paper, we direct a complete multidisciplinary writing survey with a plan to recognize the basic issues associations may have to consider while actualizing dashboards. Dashboards are probably going to succeed and take care of the issues of introduction organization and data load when certain perception standards and highlights are available (for example high information ink proportion and drill down highlights). We suggest that dashboards accompany some degree of adaptability, for example permitting clients to switch between elective introduction designs. Additionally, some hypothesis driven direction through pop-ups and alerts can assist clients with choosing a fitting introduction design.In this dashboard user can get notes of all subjects as well as all the stuff which help him grabbing a good job and also provide internships notification to users.The machine learning helps them what they require and the best result will come for them to support them.This also give the option of chatting so they can chat among the other users for any help.This also use cloud for saving their data and for faster access.So, this dashboard use web development, cloud and machine-learning and the languages for this are mainly Html,css,Bootstrap,Javascript and Php and some sqlUsers will provide the notification of many events like exam and hackathon through this dashboard.